Ambiguity and gender in the new novel of Brazil and Spanish America : a comparative assessment - Payne, Judith A., 1942- (Book collections on Project MUSE., 1993)
In this first book-length study to compare the "new novels" of both Spanish America and Brazil, the authors deftly examine the differing perceptions of ambiguity as they apply to questions of gender and the participation of females and males in the establishment of Latin American narrative models. Their daring thesis: the Brazilian new novel developed a more radical form than its better-known Spanish-speaking cousin because it had a significantly different approach to the crucial issues of ambiguity and gender and because so many of its major practitioners were women. As a wis